COMPARISON OF UPPER EXTREMITY MUSCLE STRENGTH BETWEEN PATIENTS WITH STABLE AND EXACERBATED CHRONIC OBSTRUCTIVE PULMONARY DISEASE AT A HOSPITAL IN MEDAN - Rocky Malindo Sidabutar; Amira Permatasari Tarigan; Pandiaman Pandia; Taufik Ashar (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
One of the main complications in patients with COPD is muscle weakness or atrophy, which becomes more pronounced during exacerbations, leading to a decline in quality of life, prognosis, and an increased risk of future exacerbations. This study compared upper limb muscle strength between stable COPD patients and those experiencing exacerbations. A cross-sectional study design was used, with an independent sample t-test to compare the mean values of two unpaired groups. Sampling was conducted using a non-probability consecutive sampling technique. Researchers assessed upper limb muscle strength using a Hand-grip Dynamometer on a predetermined sample size that met the inclusion and exclusion criteria. The results showed a significant correlation between the history of exacerbations within the past year and COPD in both groups (p < 0.05). Upper limb muscle strength in the exacerbation group was lower than in the stable COPD group. The independent t-test yielded a p-value of 0.001, indicating a significant difference in upper limb muscle strength between the stable and exacerbation COPD groups.